Local area high speed networks - Feit, Sidnie (Mtp Ser., 2000)
There is a great deal of change happening in the technology being used for local networks. As Web intranets have driven bandwidth needs through the ceiling, inexpensive Ethernet NICs and switches have come into the market. As a result, many network professionals are interested in evaluating these new technologies for implementation consideration. If you are looking for advice from experts who can help you realistically compare and decide how to use the options before you. Often, books on this subject are too varied in subject matter, attempting to cover to many subjects in the book. This book addresses the topic of Ethernet Networking from a planning perspective to a bit analysis of the Ethernet packets. It explains in detail information in the new network administrator would find it necessary to know.